2015
DOI: 10.1177/2165079915593249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Socio-Demographic Features, Work-Related Conditions, and Level of Anxiety Among Turkish Primary Health Care Workers

Abstract: The purpose of this study was to investigate the relationship among Turkish primary health care workers' socio-demographic characteristics, working conditions, and anxiety. A cross-sectional study was conducted with 88 of 103 (85.4%) eligible health care workers from the city of Mugla participating. The participants' average age was 31 years, 85.2% were university graduates, 30.7% were nurses, and 64.8% had been working between 11 and 20 years at the time of the study; 93.6% worked 8 hours each day or less. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Although a significant association was found in these researches, there were discrepancies in the level of stress exhibited by male and female nurses. While some concluded that, female nurses rated a higher general stress score (Dab et al, 2015;Biswas & Naidu, 2019;Makhaita et al, 2014;Caruso et al, 2017), others reported a higher stress level in male workers (Picakciefe et al, 2015;Fuente et al, 2018b;Lee & Cho, 2016). Female nurses are more stressed because, a greater number of the population of women and children visit the hospital on a daily basis and require the services of female nurses, who also have family and home responsibilities more than males (Jacobs et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant association was found in these researches, there were discrepancies in the level of stress exhibited by male and female nurses. While some concluded that, female nurses rated a higher general stress score (Dab et al, 2015;Biswas & Naidu, 2019;Makhaita et al, 2014;Caruso et al, 2017), others reported a higher stress level in male workers (Picakciefe et al, 2015;Fuente et al, 2018b;Lee & Cho, 2016). Female nurses are more stressed because, a greater number of the population of women and children visit the hospital on a daily basis and require the services of female nurses, who also have family and home responsibilities more than males (Jacobs et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dua explains this concept that, older employees have reached a stage where career development is no longer their major concern, and hence a number of job characteristics which may cause stress to younger staff, who have their career ahead of them, do not cause stress to older staff. Metin in his research realized that, older nurses have a high risk of anxiety (Picakciefe et al, 2015). Some researchers did not record any significant association between age and stress (Sabzi et al, 2017;Romano et al, 2015).…”
Section: Age and Stressmentioning
confidence: 98%